Economic Aspects for Ensuring Justice in the Context of the Industrial Development System Formation - DREMOVA, Ekaterina V. (Journal of Advanced Research in Law and Economics, 2019)
History knows many revolutions throughout the existence of mankind. Currently, all over the world there are changes concerning different spheres of public life, initiated by high-tech improvement of production technologies. This will lead the world to the Fourth industrial revolution, and, according to many experts, it has already begun. The fourth industrial revolution, or ‘industry 4.0’– is the projected changes in all spheres of public life, due to the current trend towards automation and information exchange in production technologies. This term was introduced by the President of the world Economic Forum Klaus Schwab. According to his vision, this is the concept that we are on the threshold of a new era, where the virtual world is combined with the physical through technology. This is the fourth global industrial era to come since the first industrial revolution of the eighteenth century. It is expected that these transformations will be supported by technologies such as cyberphysical systems, the Internet of things, artificial intelligence, robotics, cloud technology, 3D printing, and quantum computing.